EXPLORING CHALLENGES IN ACADEMIC WRITING: A CASE STUDY OF FINAL-YEAR ENGLISH EDUCATION STUDENTS - Aminah, Mimin; Iskandar, Ifan; Dewanti, Ratna (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Academic writing is a critical skill in higher education, particularly in English Education programs where students are expected to produce undergraduate theses. Despite its importance, many students struggle to meet academic standards in writing. This study aims to explore the challenges faced by final-year students in writing their thesis introductions. Using a qualitative case study design, data were collected through semi-structured interviews with six final-year English Education students and document analysis of their thesis drafts. Thematic analysis revealed four major challenges: difficulty initiating the writing process, limited academic vocabulary, insufficient supervisory support, and psychological pressure. These findings highlight the interplay between cognitive, linguistic, and affective factors in shaping writing performance. The study contributes to a deeper understanding of writing struggles in EFL contexts and offers pedagogical implications for academic writing instruction. It recommends enhanced scaffolding, targeted vocabulary instruction, and improved supervision practices to better support students' writing development.